The Penetapan Cost Operasional dan Honor : Pengacara Di Kantor Dsi Law Firm Banda Aceh Menurut Konsep Ujrah - fadillah, Nazila; Hasan Sulaiman, Badri; Eriyanti, Nahara (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2026)
This study examines the determination of operational costs and attorney fees at DSI Law Firm Banda Aceh based on the concept of ujrah. To date, there is no standardized regulation regarding the amount of attorney fees in Indonesia. As a result, factors such as the complexity of a case and the client’s financial condition significantly influence legal service rates, which may lead to uncertainty (gharar) and potential injustice in the attorney–client relationship. The study focuses on how operational costs and attorney fees are established, and how the concept of ujrah can serve as a foundation of fairness in this practice. The research employs a normative juridical approach combined with field research through interviews with attorneys at DSI Law Firm, as well as library research as a source of secondary data. The findings indicate that the determination of attorney fees at DSI Law Firm is carried out through an agreement between the attorney and the client, taking into account the type of case, its level of complexity, the attorney’s experience and reputation, the duration of case handling, the client’s economic condition, and the location of the court. The fee structure may be provided in the form of a lump sum and may also include a success fee, while operational costs are separated and calculated based on actual needs in a transparent manner. This pattern aligns with the principles of ujrah, which emphasize justice, propriety, feasibility, and the prohibition of imposing irrelevant fees. In conclusion, attorney fees should reflect a proportional value of services provided, in accordance with the principles of ujrah in fiqh muamalah. The study recommends the establishment of ethical guidelines or standards for determining attorney fees in order to ensure fairness, transparency, and legal certainty, both from the perspective of Indonesian positive law and fiqh muamalah.